Development and validation of the coach knowledge questionnaire: measuring coaches` professional, interpersonal and intrapersonal knowledge - Quinaud, R. T.; Backes, A. F.; Andrade do Nascimento Junior, J. R.; Carvalho, H. M.; Milistetd, M. (International Journal of Sport and Exercise Psychology, 2022)
The study aimed to develop and validate the Coach Knowledge Questionnaire (CKQ). Study 1 included the CKQ development and content validity, using an expert panel. In this study, acceptable values of content validity were found. In Study 2, the Exploratory Factor Analysis with 230 Brazilian coaches was tested. Within this study, evidence for a preliminary construct validity was provided. Study 3 included 164 Brazilian coaches who completed the CKQ. Evidences for the construct validity through Confirmatory Factor Analysis and acceptable values for convergent validity, discriminant validity and internal reliability were found in this study. Study 4 included 45 Brazilian coaches that completed the CKQ. Within this study, acceptable values for the concurrent validity and test-retest reliability were provided. In Study 5, multilevel regressions were used to verify the CKQ dimensions` sensitiveness as a part of the validation process based on the responses of 394 Brazilian coaches. Multilevel models suggest a substantial effect size considering coaches` competitive level and years of experience in the professional & interpersonal knowledge dimension and low effect size of years of experience in the intrapersonal knowledge dimension. The present study highlights the validity of the Coach Knowledge Questionnaire, which could be considered an important instrument to understand sports coaches` knowledge.